A general analytical model based on elastic foundation beam theory for adhesively bonded DCB joints either with flexible or rigid adhesives. (September 2016) - Cabello, M.; Zurbitu, J.; Renart, J.; Turon, A.; Martínez, F.
Graphical abstract: Abstract: A new general analytical model based on elastic foundation beam theory is proposed for adhesively bonded double cantilever beam (DCB) specimens. The new model accounts for any stress state (from plane stress to plane strain) in the adhesive and therefore, the model is able to predict the mechanical response of a DCB specimens whatever the adhesive type (from rigid to flexible), the stress state, and the width/thickness relationship of the specimen are. The model is validated with DCB tests for flexible Silkron-H100 and stiff Araldite-2021 adhesives. A comparison with other models from the literature demonstrates that more accurate predictions in terms of stress distribution in the middle plane of the adhesive layer, adherend deflections and load predictions are obtained. The model is especially suitable when flexible adhesives and/or thick adhesives are used. In addition, a new method to accurately obtain Poisson's ratio for flexible adhesives is proposed.